Human aortic valve interstitial cells obtained from patients with aortic valve stenosis are vascular endothelial growth factor receptor 2 positive and contribute to ectopic calcification - Xu Liu; Zaiqiang Yu; Kazuyuki Daitoku; Ikuo Fukuda; Shigeru Motomura; Tomoh Matsumiya; Tadaatsu Imaizumi; Ken-Ichi Furukawa; Kazuhiko Seya (Elsevier, 2021)
Since aortic valve stenosis (AVS) is the most frequent and serious valvular heart disease in the elderly, and is accompanied by irreversible valve calcification, medicinal prevention of AVS is important. Although we recently demonstrated that human aortic valve interstitial cells (HAVICs) obtained from patients with AVS were highly sensitive to ectopic calcification stimulation, the cell types contributing to calcification are unknown. We aimed to immunocytochemically characterize HAVICs and identify their contribution to valve calcification. HAVICs were isolated from patients with AVS and cultured on non-coated dishes. Immunocytochemical features and HAVIC differentiation were analyzed in passage 1 (P1). The immunohistochemical features of the calcified aortic valve were analyzed. Most cultured P1 HAVICs were CD73-, CD90-, and CD105-positive, and CD45-and CD34-negative. HAVICs were vascular endothelial growth factor receptor 2 (VEGFR2)-positive; however, approximately half were α-smooth muscle actin (SMA)-positive, colonized, and easily differentiated into osteoblastic cells. Calcified aortic valve immunohistochemistry showed that all cells were positive for VEGFR2 and partly α-SMA. Further, VEGFR2-positive cells were more sensitive to tumor necrosis factor-α-induced ectopic calcification with or without α-SMA positivity. We conclude that HAVICs obtained from patients with AVS are VEGFR2-positive undifferentiated mesenchymal cells and may contribute to aortic valve ectopic calcification.